The study of inter-relationship among secondary hyperparathyroidism and vitamin D3 deficiency in obese diabetics and obese non-diabetic patients - Imad Jassim Mohammad; Soheila Kashanian; Ronak Rafipour; Husam Aljwaid; Sadegh Hashemi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Adiposity is connected to vitamin D3 (Vit. D3) deficiency and hyperthyroidism. Type 2 diabetes (T2D) is associated with Vit. D3 deficiency. Our study aims to assess the inter-relationship among Vit. D3 deficiency and secondary hyperparathyroidism in obese diabetic and non-diabetic patients.Methods: Our study included 90 patients (45 obese type 2 diabetics and 45 obese non-diabetics as control). Serum Vit. D3, serum parathyroid hormone (PTH), calcium, leptin, fasting blood sugar (FBS), serum insulin, insulin resistance (HOMA-IR), hemoglobin A1C (HbA1c), and body mass index (BMI) were measured.Results: The levels of Vit. D3 deficiency were 100% in obese diabetics and non-diabetic patients 17.43 ±3.94 and 13.95 ±4.60, respectively. The association was inversely related to BMI in the obese diabetic patients (r=-0.36, P=0.01) and non-diabetic (r=-0.18, P=0.23). While the correlation was positive as well as significant (r=0.49, P